2018
DOI: 10.3382/ps/pex300
|View full text |Cite
|
Sign up to set email alerts
|

Screening lactic acid bacteria to manufacture two-stage fermented feed and pelleting to investigate the feeding effect on broilers

Abstract: Bacillus subtilis var. natto N21 (BS) and different lactic acid bacteria were applied to produce two-stage fermented feeds. Broilers were fed these feeds to select the best fermented feed. The selected fermented feed was pelleted and investigated for its effects on growth performance, carcass traits, intestinal microflora, serum biochemical constituents, and apparent ileal nutrient digestibility. Trial 1 involved three hundred thirty-six 1-d-old broilers with equal numbers of each sex, randomly assigned into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…In this study, the lambs fed FSM- and L-FWB-supplemented diet had a decreased level of BUN while they had an increased content of serum total protein and Glo, which suggested an enhancedment of the dietary protein bioavailability and improved immune condition of the lambs due to the supplementation of fermented feeds [ 24 ]. Yeh et al [ 27 ] found that pelleted fermented feed improved broiler growth performance, which may be due to the higher digestible amino acid content. Consistent results were reported that lambs in the improved growth performance group had a statistically lower concentration of BUN [ 28 ] and a higher concentration of Glu [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the lambs fed FSM- and L-FWB-supplemented diet had a decreased level of BUN while they had an increased content of serum total protein and Glo, which suggested an enhancedment of the dietary protein bioavailability and improved immune condition of the lambs due to the supplementation of fermented feeds [ 24 ]. Yeh et al [ 27 ] found that pelleted fermented feed improved broiler growth performance, which may be due to the higher digestible amino acid content. Consistent results were reported that lambs in the improved growth performance group had a statistically lower concentration of BUN [ 28 ] and a higher concentration of Glu [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ability of B. velezensis 157 to degrade ANFs and improve nutritional quality of SBM warrants further exploration, especially as part of a two-stage fermentation strategy combining both aerobic and anaerobic SSF (first stage, aerobic; second stage, anaerobic fermentation) to ultimately degrade ANFs and enhance SBM nutritional value. To date, only a few studies have already been reported for the processing of agro-industrial waste using pairs of organisms to optimize the quality of fermented feed, such as Bacillus subtilis and Enterococcus faecium (Shi et al 2017a ), Bacillus subtilis and Saccharomyces cerevisiae (Chen et al 2009 ), and Bacillus subtilis and Bacillus coagulans (Yeh et al 2018 ). However, applications involving feed fermentation by B. velezensis have not yet been reported and potential beneficial effects of fermentation on ANFs, dynamic changes in physicochemical characteristics, microorganisms and metabolites of SBM during a novel two-stage SSF process warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Production of FF from human food production wastes has attracted significant interest because microbial fermentation can be undertaken using a wide range of substrates, preserves the nutrients, degrades antinutritional factors, and limits the growth of pathogens and mycotoxin content [ 17 ]. The addition of exogenous probiotics and, therefore, the extracellular enzymes they secrete, can enhance the production of FF by preventing decomposition, degrading macronutrients, improving overall nutritional value, improving sensory characteristics, and exerting a positive effect on the microbiome of the animal gastrointestinal tract that enhances animal health and productivity [ 3 , 17 , 18 , 19 ]. For example, the application of Lactobacillus plantarum to the fermentation of cauliflower leaf waste increased the RA of lactic acid bacteria [ 20 ], thereby resulting in more efficient lactic acid fermentation, reduced proteolysis, and reduced dry matter (DM) loss [ 3 ].…”
Section: Introductionmentioning
confidence: 99%